2008
DOI: 10.1080/10641960701815804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Telmisartan and Amlodipine on Home Blood Pressure by Monitoring Newly Developed Telemedicine System: Monitoring Test by Using Telemedicine. Telmisartan's Effect on Home Blood Pressure (TelTelbosu)

Abstract: We have developed a new home blood pressure (BP) monitoring system by using cellular telephone and the Internet. All data of home BP and pulse rate were directly collected by I-converter date collecting system and sent online to a main server constructed in a central data center. The home doctor can monitor the exercise data of each patient by using this system. This home BP monitoring system was directly connected to the Internet by using application service provider technology (ASP). Anytime and anywhere, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…12, 37, 38, 40 The effects of different antihypertensive drug classes on the changes in clinic and home BP (using morning dosing) were evaluated for calcium channel blockers (6 studies), 12, 16, 17, 25, 35, 37 angiotensin converting enzyme inhibitors (5 studies), 13, 14, 18, 21, 22 and angiotensin II receptor blockers (7 studies). 18, 20-22, 24, 33, 41 Finally, we were able to compare the reductions of home BP with those of 24-hr BP in 7 articles 18, 20, 22, 25, 26, 32, 39 , and with daytime BP and nighttime BP in 5 articles. 22, 25, 26, 32, 39 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12, 37, 38, 40 The effects of different antihypertensive drug classes on the changes in clinic and home BP (using morning dosing) were evaluated for calcium channel blockers (6 studies), 12, 16, 17, 25, 35, 37 angiotensin converting enzyme inhibitors (5 studies), 13, 14, 18, 21, 22 and angiotensin II receptor blockers (7 studies). 18, 20-22, 24, 33, 41 Finally, we were able to compare the reductions of home BP with those of 24-hr BP in 7 articles 18, 20, 22, 25, 26, 32, 39 , and with daytime BP and nighttime BP in 5 articles. 22, 25, 26, 32, 39 …”
Section: Methodsmentioning
confidence: 99%
“…12-41 The full text of those papers identified as potentially relevant on the basis of their titles and abstracts was reviewed by 2 independent investigators (JI and DJC). The criteria for papers to be included in the present meta-analysis were as follows: (1) study evaluated the effect(s) of at least one antihypertensive drug therapy, (2) results published for both home BP and clinic BP, pre- and post-treatment, (3) home BP measured using a semiautomatic or automatic upper-arm cuff oscillometric device, and (4) home BP measured in the morning and/or evening according to the guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of telmisartan on the 24-hour BP values consist not only of lowering the daytime and nighttime BP, but also effectively controlling BP variability [28,29] , which has been shown to be closely correlated with PWV [11] , target-organ damage [30] and the incidence of cardiovascular events and mortality independent of the absolute BP load [31] . Previous studies have shown that the inhibitory effects of telmisartan on BP variability were associated with a reduction in sympathetic nerve activity in hypertensive patients with overt nephropathy [28] .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, such data have been transmitted via telephone lines or the internet, and are widely used for decision making [61][62][63][64][65] and clinical pharmacological evaluations. 65,66 Improvements in BP control by means of such telemedicine have been reported. 61,64,[67][68][69][70][71] 4) HOME BP AND BP CONTROL The Japanese and International guidelines recognize home BP measurements as an optimal tool for long-term BP control.…”
Section: ) Home Bp and Prognosismentioning
confidence: 99%